Cooperation and effort in group contests - Gil S. Epstein; Yosef Mealem (Bar-Ilan University, Department of Economics, 2011)
We consider a two group contest over a group specific public good comparing two situations: (i) when all players act independently; and (ii) when the players of each group cooperate. This comparison leads us to the conclusion that it is possible for one group to contribute more (and have a higher expected payoff) in the non-cooperative regime than in the cooperative regime.
Keywords: D72; C72; H41; 330; contests; rent seeking; public good; easy-riding; Öffentliche Güter; Rent-Seeking; Nichtkooperatives Spiel; Theorie